Targeted DNA oxidation by LSD1–SMAD2/3 primes TGF-β1/ EMT genes for activation or repression. Issue 16 (22nd July 2020) - Pezone, Antonio; Taddei, Maria Letizia; Tramontano, Alfonso; Dolcini, Jacopo; Boffo, Francesca Ludovica; De Rosa, Mariarosaria; Parri, Matteo; Stinziani, Stefano; Comito, Giuseppina; Porcellini, Antonio; Raugei, Giovanni; Gackowski, Daniel; et al.
Abstract: The epithelial-to-mesenchymal transition (EMT) is a complex transcriptional program induced by transforming growth factor β1 (TGF-β1). Histone lysine-specific demethylase 1 (LSD1) has been recognized as a key mediator of EMT in cancer cells, but the precise mechanism that underlies the activation and repression of EMT genes still remains elusive. Here, we characterized the early events induced by TGF-β1 during EMT initiation and establishment. TGF-β1 triggered, 30–90 min post-treatment, a nuclear oxidative wave throughout the genome, documented by confocal microscopy and mass spectrometry, mediated by LSD1. LSD1 was recruited with phosphorylated SMAD2/3 to the promoters of prototypic genes activated and repressed by TGF-β1. After 90 min, phospho-SMAD2/3 downregulation reduced the complex and LSD1 was then recruited with the newly synthesized SNAI1 and repressors, NCoR1 and HDAC3, to the promoters of TGF-β1-repressed genes such as the Wnt soluble inhibitor factor 1 gene ( WIF1 ), a change that induced a late oxidative burst. However, TGF-β1 early (90 min) repression of transcription also required synchronous signaling by reactive oxygen species and the stress-activated kinase c-Jun N-terminal kinase. These data elucidate the early events elicited by TGF-β1 and the priming role of DNA oxidation that marks TGF-β1-induced and -repressed genes involved in the EMT.